Expert GeoServer : Build and Secure Advanced Interfaces and Interactive Maps. - Mearns, Ben (Packt Publishing Ltd, 2018)
In this book, you'll learn how to publish geospatial processing algorithms through WPS, and put your GeoServer-based web application into fast, user-friendly, and secure production. By the end of this book, you will be able to deploy a professional-quality secure, and user-specific GeoServer-backed web mapping and processing application ...